2017
DOI: 10.1097/md.0000000000006247
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of corneal crosslinking for central and paracentral keratoconus

Abstract: Background:The aim of the study was to compare the therapy of corneal collagen crosslinking (CXL) for central and paracentral keratoconus.Methods:64 eyes of 43 central keratoconus patients whose highest power of the cornea located in the central 3 mm zone and 24 eyes of 16 paracentral keratoconus patients whose highest power located out of the central 3 mm zone received standard corneal CXL were included. Maximum keratometry (Kmax) and astigmatism according to topography, uncorrected distant visual acuity (UDV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“… 1 , 8 , 20 , 21 In the current study, the central KCs exhibited lower average values for the preoperative CDVA, with higher K-max values (0.25 ± 0.04 log MAR and 56.6 D) compared to paracentral KC (0.1 ± 0.2 log MAR and 53.84 D), which could explain these results. The greater improvement in the CDVA in the central cones is in accordance with what has been published by other authors, 22 , 23 and this may be due to the fact that the central area is closer to the radiation of the CXL, so the intensity of radiation is higher than in the paracentral region, plus the depth does not appear to be homogeneous within the treatment area, exhibiting a decrease towards the periphery of the cornea. 24 …”
Section: Discussionsupporting
confidence: 91%
“… 1 , 8 , 20 , 21 In the current study, the central KCs exhibited lower average values for the preoperative CDVA, with higher K-max values (0.25 ± 0.04 log MAR and 56.6 D) compared to paracentral KC (0.1 ± 0.2 log MAR and 53.84 D), which could explain these results. The greater improvement in the CDVA in the central cones is in accordance with what has been published by other authors, 22 , 23 and this may be due to the fact that the central area is closer to the radiation of the CXL, so the intensity of radiation is higher than in the paracentral region, plus the depth does not appear to be homogeneous within the treatment area, exhibiting a decrease towards the periphery of the cornea. 24 …”
Section: Discussionsupporting
confidence: 91%
“…In addition to the biomechanical properties differences, the radiation beam pattern of the previous generation of the CXL devices plays a critical role, causing different energy absorption between central and paracentral cornea, more crosslinking effect, and, by time, flattening effect on the central cornea rather than cone apex. 16,[21][22][23] The uneven energy delivery can be easily understood looking at demarcation line, deeper in the center and gradually becomes superficial going toward the periphery. 15,16,22 The top-hat or umbrella-like beam produced by a newer CXL device significantly improved the energy management, delivering a more even amount of radiation from center to periphery and improving the crosslinking effect in the apex zone.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors demonstrated that cone location is one of the most important parameters involved in corneal flattening after CXL, reporting that more topographic flattening occurs in eyes with centrally located cones. 15,16 We compared the results of the STARE-X protocol in centrally and paracentrally located keratoconus, demonstrating visual and refractive improvement maintained at 2 years after treatment in both groups, and a statistically significant change in HOAs was assessed (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique is based on the absorption of UVA radiation by the cornea after the riboflavin is taken in absorbed by the stroma. This technique can increase the corneal strength and stability by inducing cross-links at the corneal stroma [15]. However, the technique does not increase the visual function of the patient.…”
Section: Discussionmentioning
confidence: 99%